Optimization of drying parameters and texture properties of winter jujube slices by radio frequency combined with hot air - Li, Yang; Yang, Chenyan; Cao, Shuaitao; Guan, Ruijie; Zhang, Bowen; Yao, Xuedong; Wang, Qiang; Dong, Wancheng; Huang, Yong (Frontiers in Nutrition, 2025)
In order to improve the drying quality of winter jujube slices and find the best drying process parameters, RF + HA (radio frequency combined hot air) drying technology was used in this study to study the effects of plate spacing, RF application time, and RF interval time on the quality of winter jujube slices. Vitamin C (VC) content, red and green value (a*), and drying rate (DR) were used as quality indexes, and the changing trend of texture properties was analyzed. According to the conclusion of the single-factor experiment, the orthogonal experiment is carried out, and the parameters of each factor in the orthogonal experiment are optimized by the comprehensive balance method and matrix analysis method. The results showed as follows: (1) Plate spacing, RF application, and interval time all significantly affected the drying properties in the single-factor test (p < 0.05). The VC content of winter jujube slices increased and then decreased with the increase in the three factors. (2) In the orthogonal test, the order of influence of each factor on the quality of the winter jujube tablet is plate spacing > RF interval time > RF application time. The optimum RF heat treatment parameters are plate spacing of 100 mm, RF application time of 3 min, and RF interval time of 2 min. Under these conditions, the VC content of the winter jujube slices was 258.35 mg/100 g, a* was −9.47 and the DR was 0.64 g/min. (3) RF + HA has more advantages in shortening drying time and maintaining shape, reducing hardness by 12.6 ~ 18.7% and crispiness by 13.8 ~ 20.4%, the microstructure of jujube slices shows a regular honeycomb shape. The research results provide a new drying combination mechanism and process optimization scheme for improving the drying technology of winter jujube slices in industrial production.